Use of hyperbaric oxygen therapy in the treatment of osteoradionecrosis of the maxilla in patients with head and neck cancer (Research, Society and Development, 2022)
This study aimed to understand how hyperbaric oxygen therapy can act in the treatment of osteoradionecrosis of the jaws in patients with head and neck cancer. A total of 266 publications were found. After applying the inclusion and exclusion criteria, 19 articles were selected. Osteoradionecrosis is a condition with great potential for bone destruction, and therefore, many methods for treatment have been vehemently studied. Although the mechanism of action of hyperbaric oxygen therapy is not fully understood, it is known that the physiochemistry that drives the action is a result of two factors: 100% inspired oxygen and exposure to high atmospheric pressure. In addition, oxygen when present in larger quantities in the body can act to heal necrotic regions, oxygenating regions where hypoxia and hypoperfusion have occurred. However, this therapy is not totally innocuous and has significant issues for the patient, among them, the limitation of its access, and with this, the cost for oxygen therapy is very high. The negative impact that osteoradionecrosis has on oncology patients can be seen, and how hyperbaric therapy can act in the treatment of necrosis caused by oncotherapy in patients with head and neck cancer, due to its numerous effects on oxidative metabolism. In contrast, it is necessary to correctly evaluate the indication of the treatment, because the therapy has relevant adverse effects that deserve attention.